Notts rallies them from all over Britain - Abd Razak, Dzulkifli (2006)
The Notts Games held in Britain last week for the 21st time brought together Malaysian students studying there for fun, games, food and free exchange of ideas. Three Malaysian ministers took time to be there. MOST Malaysians have not heard of the Notts Games despite it being around for more than two decades. It stands for the Nottingham Games, an effort by Malaysian students studying at the University of Nottingham. Over the years, students from other universities got involved too. Their aim was simple: To get as many Malaysian students as possible to interact, especially the new ones who have just set foot on the campus or Britain for that matter. Year after year, the students have kept at it, with support from various quarters, notably the Malaysian Ministry of Education the Malaysian Students Department (Britain) and, recently, the Ministry of Higher Education.